Problems of Theory and Practice of Synthetic Stylistics in Uzbek Compound Sentences - Xolov Siyovush Atabulloyevich (Zien Journals, 2022)
This article discusses the theory of synthetic stylistics in Uzbek compound sentences, its application in practice, examples, stylistic errors and similar issues.
Keywords: Compound sentence; conjunction; pronoun; synthetic stylistics